Hubungan Self Awareness dengan Komunikasi Interpersonal Mahasiswa S1 Keperawatan - Munawaroh, Siti; Susanti, Sri; Dwirahayu, Yayuk (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Interpersonal communication is very important for nurse students. to do by doing self-awareness beforehand so they can understand other people and not cause misunderstandings and hinder further interpersonal relationships. Before communicating, students should carry out self-awareness first so they can understand other people, not misunderstand and hinder further interpersonal relationships. The ability to self awareness determines the success of interpersonal communication because someone who is sensitive to himself and his emotions will have high sensitivity when communicating. This study aims to determine the relationship between students' ability to do self-awareness with interpersonal communication. Methods: This research is a descriptive correlation research with a cross sectional research design. Samples were taken by simple random sampling of 46 respondents in semester 4 students of Bachelor of Nursing Study Program. The analysis test used the chi square test and a significance level of 5%. Results: Respondents who were not good at self awareness were 20 respondents (43.5%). Respondents who were not good at interpersonal communication were the same as the number of respondents who were good at interpersonal communication, namely 23 respondents (50%) each. The results of the chi-square test obtained a p value of 0.015, which means that Ho was rejected. Conclusion: There is a relationship between self awareness and interpersonal communication in undergraduate nursing students. It is hoped that the institution will develop a curriculum on communication because communication is very important for the success of nursing care in hospitals